Synthesis of random copolymers of 4-vinylpyridine with n-octadecyl acrylate/n-octadecyl methacrylate by metal-free ATRP - Loc Tan Nguyen; Duc-Anh Song Nguyen; Thuy Thu Truong; Le-Thu Thi Nguyen (Vietnam Journal of Science, Technology and Engineering, 2020)
Poly(4-vinylpyridine-r-n-octadecyl acrylate) and poly(4-vinylpyridine-r-n-octadecyl methacrylate) were successfully synthesised via atom transfer radical polymerization (ATRP) using 10-phenylphenothiazine as the photo-induced catalyst. The resulting copolymers were structurally characterised by proton nuclear magnetic resonance (1H NMR) and the interactions were analysed by Fourier-transform infrared (FTIR) spectroscopy.